Structural and mechanical heterogeneities of fine-grain steel welded joints used in construction of rail vehicles - Bozkurt, Fatih (Univerzita Pardubice, 2015)
This study aims to analyze the changes of impact properties in fine grained steel after welding process. Two kind of steel were used, first one was S 355N steel and second one was Domex 700MC. Both of that steels are the type of steel with an improved yield strength and are suitable for light weight construction parts of railway vehicles. Welding was performed through metal arc welding (SMAW) methods, with optimum welding process parameters. Butt joint was used for bringing two steel plates together. The microstructure changes occurring during the welding process were analyzed with scanning electron microscopy (SEM). Hardness measurements were performed started from welding pool and continued to fusion zone, heat affected zone and base material respectively. To determine the dynamic fracture yield strength and absorbed impact energy, samples were prepared for instrumented Charpy test which were taken from steel plates. All of the samples were evaluated according to EN ISO 14556:2000 Steel, Charpy V Notch Pendulum Impact Test ? Instrumented Test Method. After impact test, fractography evaluation was performed to distinguish the fracture mode and influence of primary heterogeneity of steel. The dynamic strength and fracture behavior changes after welding process were summarized; substantial degradation process was find out in Domex 700MC steel.
Keywords: SMAW; heterogeneities of fine grain steel; welded joints; construction of rail vehicles; Instrumented Charpy Test; impact energy; heterogenity jemnozrnné oceli; svarové spoje; konstrukce kolejových vozidel; instrumentovaná Charpyho zkouška; rázová energie